Pre-treatment of Flowers Extract of Abelmoschus manihot Medicus on Ischemia/Reperfusion Renal Injury in Rats - O, Jinsong; O, Cholyong; Paek, Sinhyok; Ri, Yongsu; Kang, Yongjae; Kim, Yongjun; Han, Songchan; Jang, Hyon-Song (Medical Science Journal for Advance Research, 2025)
Background and Aim: The purpose of this study is to provide a basic data with the use of flowers extract of Abelmoschus manihot (Linnaeus) Medicus (Malvaceae) (AM) as a herbal agent against renal oxidative stress. Materials and Methods: Pre-treatment effect of flowers extract of AM in rat with renal ischemia/reperfusion(I/R) injury was investigated. Renal I/R injury in rat were induced by clamping of the left and right renal arteries for 45 min followed by 24 h of reperfusion after administration of flowers extract of AM for 30 days. The effect of flowers extract of AM was evaluated through the measurement of renal function and the relevant parameters of oxidative stress. Results: Renal I/R injury led to renal dysfunction as evidenced by higher serum BUN and creatinine along with increase in oxidative stress in renal tissues compared with Sham group. Pre- treatment of flowers extract of AM decreased serum BUN, creatinine, and renal MDA levels, and increased SOD, CAT and GSH-PX activities in the kidney. Conclusion: Collectively, these data indicated that flowers extract of AM could be used as a safe and natural antioxidant for the protection of oxidative stress in kidney.